The Mood-Muscle Meta Bridge (Brain Muscle Axis) - Sanjay Kalra; Saurabh Arora; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
Psychological well-being is essential for the maintenance of good metabolic health. Modern management of most chronic metabolic disorders rightly focusses on improving the health-related quality of life of persons living with disease. In this brief communication we describe the bidirectional association between muscle function and mood (psychological health), explore the various pathways that link these aspects of health, and underscore their clinical implications. This paper emphasizes the importance of maintaining good mental health through exercise and vice a versa. Keywords: Muscle function, muscle strength, sarcopenia, dysthymia, depression, physical activity.